Cell Membrane-Coated Oil in Water Nano-Emulsions as Biomimetic Nanocarriers for Lipophilic Compounds Conveyance - Martina Profeta; Concetta Di Natale; Elena Lagreca; Valentina Mollo; Paolo Antonio Netti; Raffaele Vecchione (MDPI AG, 2021)
Recently, we developed ultra-stable oil in water nano-emulsions (O/W NEs), able to carry both internal and external cargos (Somes), such as lipophilic compounds and hydrophilic coatings, respectively, that we call here NEsoSomes. O/W NEs are an excellent bioengineering tool for drug and molecules delivery, due to their ability to dissolve a large number of hydrophobic compounds and protect them from hydrolysis and degradation under biological conditions. At present, no report is available on the combination of cell membrane coatings with such nanocarriers, probably due to their typical instability feature. Since then, we have reported, for the first time, a new cell membrane (CM)-coated nanomaterial composed of membranes extracted from glioblastoma cancer cells (U87-MG) deposited on NEsoSomes, through a liquid-liquid interface method, to produce highly controllable membrane caked nano-capsules, namely CM-NEsoSomes. CM-NEsoSomes were physically characterized by dynamic light scattering (DLS) over time and their correct morphology was analyzed by confocal and transmission electron microscopy (TEM) microscopy. Moreover, CM-NEsoSomes biocompatibility was tested on the healthy model cell line, performing cell cytotoxicity and uptake assay, showing nanocarriers uptake by cells with no induced cytotoxicity.